RANCANG BANGUN VIDEO CONFERENCE HOLOGRAM BERBASIS ANDROID - Safwan; Trian Ahmadi (J-Innovation, 2020)
Video conferencing that currently exists only displays objects on media such as monitors, smartphone screens and projectors.The design of communication media that the writer will build will display the object in a hologram. Holographic mediamakes objects come alive. Android smartphone-based video conferencing will be connected to four monitor screens facingthe sides of a trapezoidal building. Where this tool will be able to be used for an interest in a meeting if the director oraudient who is unable to attend can attend the meeting wherever and whenever.